1987
DOI: 10.1203/00006450-198703000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Age-Dependent Changes of Membrane Protein 4.1: Studies in Transient Erythroblastopenia

Abstract: ABSTRACT. In high resolution sodium dodecyl sulfategel electrophoresis, the red cell protein, band 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The findings of well as the process of reticulocyte maturation. We have demonRavindranath et al (24) that children with transient red cell strated that stractan density gradient centrifugation yields sub-populations of erythrocytes with relative quantities of protein 4.la which increase with increasing cell density; cells from the most dense layers of the gradient (density > 1.1 10 g/ml) have the greatest amount of 4. la. These data indicate that such density separations provide subpopulations of red cells enriched for senescent erythrocytes.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The findings of well as the process of reticulocyte maturation. We have demonRavindranath et al (24) that children with transient red cell strated that stractan density gradient centrifugation yields sub-populations of erythrocytes with relative quantities of protein 4.la which increase with increasing cell density; cells from the most dense layers of the gradient (density > 1.1 10 g/ml) have the greatest amount of 4. la. These data indicate that such density separations provide subpopulations of red cells enriched for senescent erythrocytes.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, demonstrating a correlation between erythrocyte enzyme levels and density may confirm an enrichment of young cells at the top of a density gradient, but may not define the relative age of denser cells. Recently, studies of red cells from mouse and from man have suggested that the ratio of protein 4.la to 4.lb is an internal aplasia have exceptionally high ratios of 4.la to 4.lb indicate marker of cell age; as erythrocytes circulate, progressively more that this ratio reflects the aging process of mature red cells as protein 4. l a is present in the cells (23,24). The findings of well as the process of reticulocyte maturation.…”
Section: Discussionmentioning
confidence: 86%
“…Conversely, the percent HbA1c has been used to estimate the relative age of isolated RBC subfractions [14]. The ratio of erythrocyte membrane Band 4.1a:4.1b is increased in the aged RBC present in the hypertransfused mouse model [17] and in transient erythroblastopenia of childhood [18], and is decreased in hemolytic anemias [19]. This has lead to the use of this ratio as an age marker in human RBC [20].…”
Section: Age-dependent Changes In Red Blood Cell Propertiesmentioning
confidence: 99%
“…This has been demonstrated by increased band 4 . l a protein in RBC membrane of children with TEC (Ravindranath et al, 1987). In the present study, deformability (rheoscope) and density of RBCs were studied in seven children with TEC.…”
mentioning
confidence: 91%